IMPLEMENTATION OF THE CHILD IDENTITY CARD POLICY IN SERANG DISTRICT, BANTEN PROVINCE - Drajat Wisnu Setyawan; Djohermansyah Djohan; Muh. Ilham; Dedeh Maryani (Al-Makki Publisher, 2024)
The issuance of birth certificates for the child population in Banten Province has reached the specified target, where out of 2,923,089 child population who have birth certificates as many as 2,905,894 residents or equivalent to 99.41%. However, this is not matched by the issuance of Child Identity Cards, the percentage of coverage is still very low, which only reaches 29.78% of the entire child population who already has a birth certificate. The purpose of the research is to find out, analyze and explain the implementation of the child identity card, the determinant factors that determine and construct an effective Child Identity Card policy implementation model in Serang Regency, Banten Province. This research uses the theory of policy implementation put forward by Hamdi (2014) with the dimensions of productivity, linearity and efficiency. Determinant factors that influence policy implementation are policy substance, implementing officer behavior, network interaction, target group participation and resources. The research method used is qualitative research with a descriptive approach. Data collection techniques were carried out by interview, observation and documentation. The results showed that the implementation of the Child Identity Card policy in Serang Regency was not optimal.